Voisiko maalittaminen olla rangaistavaa? - Koivukari, Kristiina (Lakimies, 2025)
Could online shaming be criminalised? Online shaming is a new and topical issue in Finnish legal discourse. The concept of online shaming refers to hateful expressions where someone has initiated a hate campaign against another, usually on social media or on some other online platform. Besides being severely disturbing to the target, even the risk of this kind of shaming potentially affects and distorts public discussion and the public’s right to obtain information. Online shaming often consists of separate acts some of which do not constitute criminal offences, but some do. However, the range of potentially applicable criminal provisions is rather broad, and the offences are seldom serious when assessed separately. In practice, therefore, the cases are difficult to identify, investigate, and prosecute. It has been suggested that a new criminalisation is needed: For this to have the required effect, the new provision should cover all or most of the acts constituting online shaming. The author argues that such a broad criminalisation of online shaming is not possible. The principles of legality and assumption of innocence, as well as the limited possibilities to restrict the freedom of expression, prevent the criminalisation of online shaming comprehensively. The problem lies in the impossibility to define online shaming precisely enough to be able to differentiate harmful and malicious shaming from targeted criticism that should still be allowed under the freedom of expression. In addition, with an ongoing online shaming campaign, it is impossible to differentiate between acts that would constitute the offence of shaming and comments that “merely” criticise the target with no intent to shame.